Do we need more fans in the stadiums? The investigation of fan identification and attachment to the team in the case of domestic football clubs - Bodon, György; Kajos, Attila; Neulinger, Ágnes (Vezetéstudomány / Budapest Management Review, 2023)
The development of fans’ attachment to the team and the involvement of new fans are essential in a developed sports economy. In Hungary, this is a decades-old unsolved problem; new stadiums have been built with spectacular investments, the use of which should be significantly improved in the case of domestic football championships. This research examines the Mol Fehérvár FC fanbase, part of the first-class Hungarian OTP Bank Liga football championship. The purpose of this research is to examine the relationship between fan identification and attachment to the team in connection with team loyalty and fan behaviour. In the case of the fans of the investigated team, the disillusionment and the erosion of team attachment is a problem that the club should deal with to increase its brand value, the number of spectators, and, consequently, its income.